Cacao-based Agroforestry in Conservation Forest Area: Farmer Participation, Main Commodities and Its Contribution to the Local Production and Economy - Murniati, Murniati; Suharti, Sri; Yeny, Irma; Minarningsih, Minarningsih (Forest and Society, 2022)
Cacao-based agroforestry systems have been developed in the conservation forest area of Wan Abdul Rachman Grand Forest Park (WAR GFP). Previously, the forest areas were occupied by surrounding needy communities, causing land-use conflict and forest degradation. To resolve these problems, the conservation forest manager developed a conservation partnership program, giving farmers legal access to establish cacao agroforestry systems while improving forest conditions. This research aimed to study the farmers’ participation, main commodities of the cacao-based agroforestry system, and its contribution to the local production and economy. This research was conducted in 2018 and 2019. The field survey was used to characterize the agroforestry system practiced and a series of interviews with two respondent groups, stakeholders concerned with WAR GFP management (nine key informants), and cacao-based agroforestry farmers (61 respondents). The agroforestry systems were dominated by cacao trees mixed with other tree crops and forest trees with an average density of 1,169.3 ± 668.3 trees/ha. Community involvement in the agroforestry development has only reached "Placation" or level 5 of Arnstein's participation ranking, implying they are granted limited opportunities to participate in the agroforestry development. Cacao production was influenced by the cacao tree and the associated tree density. Optimal cacao production as much as 367.4 ± 357.9 kg/ha was achieved at 1,253 trees/ha of total tree density. Besides cocoa, there were 13 primary commodities, where some have contributed more than 40% to district production. Income gained from the agroforestry systems contributes significantly (75.63%) to total farmers’ income. It can fulfill households’ basic needs and has exceeded the poverty line at the national level. The cacao-based agroforestry development has become an alternative to resolve land use conflict in conservation forest areas characterized by land scarcity with a dense population